Some Characteristics of Breakfast Spreadable Cornelian Cherry (Cornus mas L.) Nectar Produced Using Potentially Probiotic Starter Culture - Duygu Alp; Samet Mısır (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it was aimed to make a breakfast spreadable Cornelian cherry nectar similar to marmalade. Lactiplantibacillus plantarum DA100 strain, which has potential probiotic properties, was added to this nectar.  It was investigated whether this strain has an effect on various sensory properties of nectar. In the study, sensory and various chemical properties of nectar produced without probiotic microorganism were determined. Since the breakfast spreadable Cornelian cherry nectar produced in our study was not exposed to high temperatures for a long time, a very low HMF of 4.290 mg/kg was determined. Vitamin C was determined as 716.800 mg/L and total phenolic content was determined as 3156.64 mg GAE/100g. In the probiotic group, the microorganism viability, which was 1.5×1010 Log CFU/mL initially, was determined below approximately 1.5×106 Log CFU/mL at the end of 5 days. In addition, coliform bacteria and E. coli were not detected in any group during this period. Contrary to the texture score, the difference between the sensory evaluation results of the probiotic-added and the control group of breakfast spreadable Cornelian cherry nectar was significant in taste, bitterness, odor and sourness. An alternative to jams and marmalades, rich in vitamin C and phenolic content, limited HMF production, and a functional product with low sugar content were tried to be obtained, and when the results obtained are evaluated, the product is thought to be promising.